Analisis Jaringan Produksi Dan Inovasi Varian Rasa Pada Kue Sus Choux - Evi Ulviah; Resya Dwi Marselina (Institut Nalanda, 2024)
Building a business network is a crucial business strategy during the startup process. Business networking refers to relationships formed through various interactions among business players, professionals, and potential financial specialists (Ferira, 2023). While some studies have explored business networks, such as the analysis of TikTok as a platform for millennial business networking, there hasn't been specific research on production networks, which is a derivative of business networks. To address this gap and the literature void regarding production networks, the author proposes a scholarly title,